Controlled Human Malaria Infection Induces Long-Term Functional Changes in Monocytes - Walk, Jona; Keramati, Farid; de Bree, L. Charlotte J.; Arts, Rob J. W.; Blok, Bas; Netea, Mihai G.; Stunnenberg, Hendrik G.; Sauerwein, Robert W. (Frontiers in Molecular Biosciences, 2020)
Innate immune memory responses (also termed ‘trained immunity’) have been described in monocytes after BCG vaccination and after stimulation in vitro with microbial and endogenous ligands such as LPS, β-glucan, oxidized LDL, and monosodium urate crystals. However, whether clinical infections are also capable of inducing a trained immunity phenotype remained uncertain. We evaluated whether Plasmodium falciparum infection can induce innate immune memory by measuring monocyte-derived cytokine production from five volunteers undergoing Controlled Human Malaria Infection. Monocyte responses followed a biphasic pattern: during acute infection, monocytes produced lower amounts of inflammatory cytokines upon secondary stimulation, but 36 days after malaria infection they produced significantly more IL-6 and TNF-α in response to various stimuli. Furthermore, transcriptomic and epigenomic data analysis revealed a clear reprogramming of monocytes at both timepoints, with long-term changes of H3K4me3 at the promoter regions of inflammatory genes that remain present for several weeks after parasite clearance. These findings demonstrate an epigenetic basis of trained immunity induced by human malaria in vivo.